Development of a self-efficacy scale for digital competences in schools - Norden, Lars-Ake; Mannila, Linda; Pears, Arnold (2017 IEEE Frontiers in Education Conference (FIE), 2017)
As computer science enters the school curricula in an increasing number of countries, teachers must prepare to integrate digital competences into their teaching. This integration is a moving target where new methods, tools and applications appear and disappear at such rates that teachers must have confidence to independently and continuously explore what is new, what is relevant and how to plan their pedagogic activities to include digital competences. In this context approaches which can be used to study self-efficacy in digital competences among school teachers are desperately needed. With such a tool in place, we can make a baseline study and then follow teachers over time to measure changes in their self-efficacy, the cause of these changes and learn how to build their digital competence self-efficacy in different ways. The same tool can also be used to measure the self-efficacy in other populations, e.g., students in teacher training programs to ensure that they obtain an adequate self-efficacy in digital competences during their studies. This paper describes the development of a self-efficacy scale in digital competences, based on the DigiComp 2.0 framework definition of digital competence. The tool focuses predominantly on digital competences relevant for teachers in school years K-9.